Implikasi Teologi Praktis Jemaat Mula-Mula Yerusalem bagi Kehidupan GPdI Eben Haezer Antutan - Frits Mokodaser; Reni Triposa; Esti Regina Boiliu (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This study discusses the life of the early church as recorded in Acts 2:42-47, which explains the practical theological standards for the church today, especially for the life of the GPdI Eben Haezer church in Antutan village. Referring to the early church in Jerusalem, we can see that the early church was full of faithfulness in teaching and deepening the word of God, close fellowship, and prayer as a way of life, as well as a very high and tangible level of social concern. This pattern of life not only reflects unity in a community centred on Christ, the head of the church, and illustrates the fullness of the Holy Spirit, but it also illustrates a balanced life between our relationship with God and our relationships with other human beings. This study uses a qualitative approach with a literature study method. The conclusion of this study reveals that emulating the life of the early church in Jerusalem will strengthen the church today, especially the GpdI Eben Haezer congregation in Antutan village, to become a church community that is faithful to the word of God, filled with the power of the Holy Spirit, and become a practical guide in faith development, fellowship, and ministry amid economic challenges and globalisation.